Is English Medium Meaningful in Pre-Primary Level in Nepal? - Miya, Farmud (Academic Voices: A Multidisciplinary Journal, 2018)
Language is a means for communication. It also helps children in their cognitive development. Intellectual (cognitive) development, the emergence of increasingly sophisticated forms or levels of understanding, reasoning, and rationality is an ongoing process of reflection, coordination, and social interaction that begins in early childhood and continues, at least in some cases, long into adulthood (Moshman, 2003).it is also regarded that whatever the children build their concept about the society in their early childhood remains throughout their life. In this process language has pivotal role. However, it is not to say that thinking (as an intellectual ability) cannot take place without language (Munn, 1951) but rather mostly, thinking is mediated by language and thus develops to a higher level of sophistication. This article focuses on the important contribution of mother tongue in the process of cognitive development and raises questions against the local decisions of using English medium in pre-primary level.